Catlin's North American Indian portfolio : hunting scenes and amusements of the Rocky Mountains and prairies of America - Catlin, George, 1796-1872 (Chatto & Windus, 1875)
Catlin's North American Indian Portfolio contains the results of his years of painting, living with and travelling amongst the Great Plains Indians. In a famous passage from the preface, Catlin describes how the sight of several Indian chiefs in Philadelphia led to his resolution to record their vanishing way of life: "the history and customs of such a people, preserved by pictorial illustrations, are themes worthy of the lifetime of one man, and nothing short of the loss of my life shall prevent me from visiting their country and becoming their historian". From 1832 to 1837 he spent the summer months sketching the tribes and then finished his pictures in oils during the winter. He painted around 600 highly realistic and powerfully projected portraits of Indians, carefully recording their costume, culture and way of life. --abebooks website.